Dorongan Motivasi Agar Kebiasaan Belajar dalam Mengatasi Problem Malas Belajar - Guna, Ahmad Saka Falwa (Universitas Negeri Makassar, 2024)
This study aimed to find out how to get rid of laziness to be motivated in learning and also to get used to learning. Eliminating laziness was very difficult to do because of the need for a process to change this attitude, changing a person's attitude requires motivation in him/her so that he/she was motivated to do learning activities independently and when someone was motivated to learn every day without being told by someone made us get used to it in study. The focus of this research was to eliminate laziness to be motivated in learning and also to get used to learning. This research used literature study and analytical studies to build a theoretical framework for this material. The conclusion of eliminating laziness was done in the first way, intention because with intention, it motivated us to complete a task supported by strong motivation. Second, determined when the deadline. Third, made targets and activity arrangements. Fourth, put anything else aside, doing so kept us focused on our previous goals. Fifth, friends, if we had friends who were diligent, they automatically affect us in terms of learning. Sixth, thought about your parents and your future. Seventh, consistent, consistently made us get used to it even if we were still learning without any assignments.